Multiscale modeling of ion diffusion in cement paste: electrical double layer effects. (February 2019) - Yang, Yuankai; Patel, Ravi A.; Churakov, Sergey V.; Prasianakis, Nikolaos I.; Kosakowski, Georg; Wang, Moran
Abstract: Understanding the mechanism of ion diffusion in hardened cement paste is of great importance for predicting long-term durability of concrete structures. Gel pores in calcium silicate hydrate (CSH) phase forms dominant pathway for transport in cement paste with low w/c ratios where the electrical double layer effects play an important role. Experimental results suggest that the effective diffusivity of chloride ions is similar as that of tritiated water (HTO) and higher than the sodium ions. This difference can be attributed to the electrical double layer near the charged CSH surfaces. In order to understand species transport processes in CSH and to quantify its effective diffusivity, a multiscale modeling technique has been proposed to combine atomic-scale and pore-scale modeling. At the pore scale, the lattice Boltzmann method is used to solve a modified Nernst Planck equation to model transport of ions in gel pores. The modified Nernst Planck equation accounts for steric and ion-ion correlation effects by using correction term for excess chemical potential computed through the results from the grand canonical Monte Carlo scheme at atomic scale and in turn bridges atomic scale model with pore scale model. Quantitative analysis of pore size influence on effective diffusivity carried out by this multiscale model shows that the contribution of the Stern layer to ion transport is not negligible for pores with diameter less than 10 nm. The developed model is able to reproduce qualitatively the trends of the diffusivity of different ions reported in literature.